U Uji Aktivitas Antifungi Ekstrak Kulit Batang Tanaman Kenanga (Cananga odorata) Terhadap Jamur Malassezia furfur - Intan, Intan; Nastiti, Kunti; Aryzki, Saftia; Darsono, Putri Vidiasari (LPPM Universitas Sari Mulia, 2024)
Background: One of the plants that is efficacious in the world of medicine is the ylang-ylang plant (Cananga odorata), namely the bark of the ylang-ylang plant which is used by the Kapuas people of Central Kalimantan to treat diseases such as tinea versicolor.Objective: To determine the identification of the antifungal activity test of the bark extract of the ylang-ylang plant (Cananga odorata) against the Malassezia furfur fungus and to determine the minimum inhibitory concentration (MIC) and minimum kill concentration (KBM) of the bark extract of the ylang-ylang plant (Cananga odorata) against the fungus Malassezia furfurMethods: Research method Using experimental methods using the Malassezia furfur fungus. Ylang ylang bark extract (Cananga odorata) was screened for phytochemicals such as alkaloids, flavonoids, terpenoids/steroids, tannins and saponins. This study used 3 treatment groups consisting of positive control (ketoconazole 200 mg), negative control (DMSO) and ylang ylang (Cananga odorata) bark extract at concentrations of 25%, 50%, 75% and 100% with disc diffusion and dilution treatments.Results: The bark extract of the ylang-ylang plant (Cananga odorata) contains several secondary metabolites such as alkaloids, flavonoids, terpenoids, tannin saponins and has inhibitory activity using the disc diffusion method with an average diameter of 25.85 mm. Antifungal testing was carried out using the dilution method with a value of MIC is 25% and there is no KBM for the Malassezia furfur fungus.Conclusion: Bark extract of the ylang-ylang plant (Cananga odorata) has antifungal activity against the fungus Malassezia furfur